Dicalcium silicate-calcium fluorosulphosilicate-dodecacalcium heptaaluminate cement clinker and preparation method thereof

Through the low-temperature sintering and grinding of dicalcium silicate-fluorosulfosilicate-dodecacium heptaalaluminate cement clinker system, the high energy consumption of cement clinker and unstable calcium sulfosilicate are solved, and the energy efficiency is achieved Reduced consumption and early intensity increase, suitable for emergency repair projects.

CN119143413AActive Publication Date: 2024-12-17UNIV OF JINAN +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411362190.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-17
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The firing of cement clinker requires a large amount of fossil fuel, which leads to high carbon dioxide emissions and energy consumption, and the structure of calcium sulfosilicate is unstable, resulting in the problem of low content in preparation.

Method used

Using dicalcium silicate-calcium fluorosulfosilicate-dodecacium heptaalaluminate cement clinker system, the sulfur silicon is stabilized by low-temperature sintering (1100~1200℃) and grinding, and the fluorine element in fluorine-containing sludge is used to stabilize sulfur silicon. Calcium acid, combined with dodecanocalcium heptaaloate, improves early strength and coagulation rate.

Benefits of technology

It effectively reduces the firing temperature and energy consumption of cement clinker, reduces carbon dioxide emissions, realizes the utilization of fluorine resources and the early strength of cement clinker, is suitable for emergency repair projects, and continues to develop mechanical strength in the later stage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143413A_ABST
    Figure CN119143413A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of cement clinker, and particularly discloses dicalcium silicate-calcium fluorosulphosilicate-dodecacalcium heptaaluminate cement clinker and a preparation method of the dicalcium silicate-calcium fluorosulphosilicate-dodecacalcium heptaaluminate cement clinker. The cement clinker is prepared from the following mineral phases in percentage by mass: 45 to 68 percent of dicalcium silicate, 14 to 26 percent of calcium fluorosulphosilicate, 12 to 22 percent of dodecacalcium heptaaluminate, 1 to 5 percent of gehlenite, 2 to 6 percent of glass phase and the balance of unreacted raw materials and inevitable impurities. The clinker system disclosed by the invention takes the fluorine-containing sludge as a raw material, so that the resource utilization of the fluorine-containing sludge is realized, the harm of fluorine to the environment is reduced, and unstable calcium sulphosilicate is converted into stable calcium fluorosulphosilicate with low firing temperature; the overall firing temperature of the cement clinker system is obviously lower than that of traditional Portland cement, so that the energy consumption is effectively reduced, and the emission of carbon dioxide is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement clinker preparation, and in particular to a dicalcium silicate-calcium fluorosulfosilicate-dodecalcium heptaaluminate cement clinker and a preparation method thereof. Background Art

[0002] In recent years, global warming has caused a series of environmental problems, such as melting glaciers, rising sea levels, species extinction and extreme weather, and greenhouse gas emissions are the main cause of climate change. The global average temperature in 2019 was 0.92℃ higher than the average from 1980 to 2010, and 1.1℃ higher than the pre-industrial level. Among them, carbon dioxide emissions are one of the most concerned greenhouse gases, and the relationship between carbon dioxide emissions and global warming has become an important topic of extensive attention and in-depth research from all walks of life around the world. Since the burning of cement clinker requires a large amount of fossil fuels, which will release a large amount of carbon dioxide and cause a large amount of non-renewable energy consumption, it is urgent to seek relevant technological breakthroughs for the carbon reduction goals of the building materials industry. Summary of the invention

[0003] The present invention provides a dicalcium silicate-calcium fluoride sulfo-silicate-dodecalcium heptaaluminate cement clinker and a preparation method thereof. The overall firing temperature of the clinker system is significantly lower than that of traditional silicate cement, thereby effectively reducing energy consumption and reducing carbon dioxide emissions. Specifically, the technical solution of the present invention is as follows.

[0004] Firstly, the present invention discloses a dicalcium silicate-calcium fluorosulfo-dodecalcium heptaaluminate cement clinker, which comprises the following mineral phases in percentage by mass: 45-68% of dicalcium silicate, 14-26% of calcium fluorosulfo-silicate, 12-22% of dodecalcium heptaaluminate, 1-5% of calcium aluminum feldspar, and 2-6% of a glass phase, with the remainder comprising unreacted raw materials, unavoidable impurities, and the like.

[0005] Secondly, the present invention discloses a method for preparing dicalcium silicate-calcium fluoride-dodecalcium heptaaluminate cement clinker, comprising the following steps: using a calcium source, a silicon source, gypsum, an aluminum source, and fluorine-containing sludge as raw materials, mixing them uniformly in proportion, and then calcining them. After completion, the calcined product is rapidly cooled, and then ground to obtain the cement clinker.

[0006] Furthermore, the proportions of the components in the raw materials are: 57-85 parts by weight of calcium source, 30-48 parts by weight of silicon source, 18-35 parts by weight of gypsum, 16-27 parts by weight of aluminum source, and 14-32 parts by weight of fluorine-containing sludge. Optionally, the fineness of each component is not less than 200 mesh.

[0007] Furthermore, the calcium source includes at least one of limestone, marl, chalk, alkali slag, carbide slag and the like.

[0008] Furthermore, the silicon source includes at least one of stripping soil, silica ash, coal gangue, clay, quartz sand, diatomaceous earth and the like.

[0009] Furthermore, the gypsum includes at least one of desulfurized gypsum, phosphogypsum, fluorinated gypsum, borogypsum, and titanium gypsum.

[0010] Furthermore, the aluminum source includes at least one of bauxite, fly ash, aluminum ash, coal gangue, etc.

[0011] Furthermore, the fluorine content in the fluorine-containing sludge is not less than 15wt.%.

[0012] Furthermore, the calcination temperature is 1100-1200° C., and the calcination time is 15-60 min.

[0013] Furthermore, the cement clinker is ground to a fineness of not less than 200 meshes.

[0014] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: (1) Compared with traditional silicate cement, calcium sulfosilicate has a lower formation temperature (below 1200°C). Therefore, using this mineral phase as a component of cement clinker can effectively reduce the firing temperature of cement clinker, reduce energy consumption and carbon emissions. However, the structure of calcium sulfosilicate is unstable and it is difficult to exist stably at high temperatures, resulting in a low content of this component in the prepared cement clinker. To this end, the present invention uses fluorine-containing sludge as a raw material, and utilizes the characteristics that the electronegativity of the fluorine element therein is greater than that of sulfur, and the attraction of fluorine to bonding electrons is greater than that of sulfur, so that fluorine enters the lattice of calcium sulfosilicate and converts it into calcium fluorosulfosilicate. This mineral phase not only has a more stable structure and can be stably retained in the cement clinker, but also maintains the characteristics of a low firing temperature. The cement clinker of the present invention is mainly composed of dicalcium silicate-calcium fluorosulfosilicate-dodecalycium heptaaluminate, which can be fired at a relatively low temperature of 1100~1200°C, effectively saving energy consumption, and also realizing the resource utilization of fluorine-containing sludge, reducing the pollution hazards of fluorine.

[0015] (2) Although the dicalcium silicate-calcium fluorosulfosilicate-dicalcium heptaaluminate cement clinker of the present invention solves the problem that the calcium sulfosilicate structure is unstable, resulting in a low content of this component in the prepared cement clinker, the present invention further finds that this cement clinker still has the problem of insufficient early strength. The dodecaluminate heptaaluminate overcomes the above problem well, effectively improves the early strength of the cement clinker of the present invention, and at the same time improves the setting rate, making the cement clinker system of the present invention also suitable for emergency repair projects. In addition, the hydration of the dodecaluminate heptaaluminate will generate Al(OH)4 -, which puts the pore fluid in an undersaturated state. In order to maintain the charge balance of the pore fluid, other mineral phases in the system begin to dissolve. Because the solubility product of calcium fluorosilicate is greater than that of dicalcium silicate at room temperature, the dissolution of calcium fluorosilicate is promoted, thereby promoting the hydration process of calcium fluorosilicate. At this time, the silicate ions and calcium ions in the pore fluid are in a relatively saturated state, thus inhibiting the dissolution of dicalcium silicate. When the hydration of calcium fluorosilicate is exhausted, dicalcium silicate begins to dissolve in large quantities, thereby enabling the later mechanical strength of the cement clinker of the present invention to continue to develop. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0017] Figure 1 This is a sample picture of the dicalcium silicate-calcium fluorosulfosilicate-dicalcium heptaaluminate cement clinker prepared in the following Example 1. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0019] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0020] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0021] Example 1 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 85 parts of limestone, 42 parts of clay, 26 parts of desulfurized gypsum, 21 parts of fly ash, and 14 parts of fluorine-containing sludge (purchased from Anhui Tongxin Recycling Resources Co., Ltd., with a fluorine content of 23.7 wt.%).

[0022] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0023] (3) The finished cake is heated to 1150°C at a heating rate of 10°C / min and calcined for 30 min, and then the calcined product is rapidly cooled by air cooling and then ground through a 200-mesh sieve to obtain cement clinker, such as Figure 1 shown.

[0024] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included 67.93% dicalcium silicate, 14.12% calcium fluoride sulfide silicate, 11.98% dodecaluminate heptaaluminate, 1.05% grossamite, 4.74% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0025] In accordance with GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 30.45 MPa, 28d compressive strength = 48.27 MPa.

[0026] Example 2 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 72 parts of limestone, 30 parts of clay, 18 parts of desulfurized gypsum, 27 parts of fly ash, and 29 parts of fluorine-containing sludge (purchased from Anhui Tongxin Recycling Resources Co., Ltd., with a fluorine content of 23.7 wt.%).

[0027] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0028] (3) The finished cake is heated to 1150° C. at a heating rate of 10° C. / min and calcined for 50 min. The calcined product is then rapidly cooled by air and then ground through a 200-mesh sieve to obtain cement clinker.

[0029] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included: 44.97% dicalcium silicate, 23.51% calcium fluoride sulfide silicate, 19.14% dodecaluminate heptaaluminate, 5.05% grossamite, 4.37% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0030] In accordance with GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 31.51 MPa, 28d compressive strength = 50.88 MPa.

[0031] Example 3 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 67 parts of limestone, 39 parts of diatomaceous earth, 32 parts of phosphogypsum, 18 parts of bauxite, and 28 parts of fluorine-containing sludge (purchased from Anhui Tongxin Recycling Resources Co., Ltd., with a fluorine content of 23.7 wt.%).

[0032] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0033] (3) The finished cake is heated to 1125° C. at a heating rate of 10° C. / min and calcined for 20 min. The calcined product is then rapidly cooled by air and then ground through a 200-mesh sieve to obtain cement clinker.

[0034] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included 52.25% dicalcium silicate, 25.09% calcium fluoride sulfide silicate, 14.33% dodecalyx heptahedralite, 3.87% grossamite, 1.95% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0035] In accordance with GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 32.04 MPa, 28d compressive strength = 52.71 MPa.

[0036] Example 4 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 76 parts of limestone, 48 parts of silica fume, 35 parts of fluorinated gypsum, 26 parts of aluminum ash, and 32 parts of fluorine-containing sludge (purchased from Anhui Tongxin Recycling Resources Co., Ltd., with a fluorine content of 23.7 wt.%).

[0037] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0038] (3) The finished cake is heated to 1100° C. at a heating rate of 10° C. / min and calcined for 60 min. The calcined product is then rapidly cooled by air cooling and then ground through a 200-mesh sieve to obtain cement clinker.

[0039] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included: 45.08% dicalcium silicate, 26.11% calcium fluoride sulfide silicate, 22.06% dodecaluminate heptaaluminate, 2.33% grossamite, 2.37% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0040] According to GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 34.06 MPa, 28d compressive strength = 53.47 MPa.

[0041] Example 5 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 79 parts of calcium carbide slag, 44 parts of quartz sand, 31 parts of titanium gypsum, 22 parts of coal gangue, and 19 parts of fluorine-containing sludge (purchased from Anhui Tongxin Recycling Resources Co., Ltd., with a fluorine content of 23.7 wt.%).

[0042] (2) Dry the above raw materials at 90°C for 10 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0043] (3) The finished cake is heated to 1200° C. at a heating rate of 10° C. / min and calcined for 35 min. The calcined product is then rapidly cooled by air cooling and then ground through a 200-mesh sieve to obtain cement clinker.

[0044] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included 57.46% dicalcium silicate, 14.02% calcium fluoride sulfide silicate, 16.37% dodecaluminate heptaaluminate, 4.98% grossamite, 6.08% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0045] In accordance with GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 29.83 MPa, 28d compressive strength = 54.95 MPa.

[0046] Example 6 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 57 parts of limestone, 46 parts of clay, 33 parts of fluorinated gypsum, 16 parts of fly ash, and 30 parts of fluorine-containing sludge (purchased from Anhui Tongxin Recycling Resources Co., Ltd., with a fluorine content of 15.1 wt.%).

[0047] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0048] (3) The finished cake is heated to 1200° C. at a heating rate of 10° C. / min and calcined for 15 min. The calcined product is then rapidly cooled by air and then ground through a 200-mesh sieve to obtain cement clinker.

[0049] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included 52.23% dicalcium silicate, 25.87% calcium fluoride sulfide silicate, 12.08% dodecalyx heptahedralite, 1.41% grossamite, 5.84% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0050] In accordance with GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 30.98 MPa, 28d compressive strength = 53.09 MPa.

[0051] Example 7 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 72 parts of limestone, 30 parts of clay, 18 parts of desulfurized gypsum, and 27 parts of fly ash.

[0052] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0053] (3) The finished cake is heated to 1150° C. at a heating rate of 10° C. / min and calcined for 50 min. The calcined product is then rapidly cooled by air and then ground through a 200-mesh sieve to obtain cement clinker.

[0054] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included: 69.78% dicalcium silicate, 3.46% calcium sulfosilicate, 7.59% dodecaluminate heptaaluminate, 6.21% monocalcium aluminate, 3.57% grossamite, 5.88% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0055] According to GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 26.12 MPa, 28d compressive strength = 42.03 MPa.

[0056] Example 8 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 85 parts of limestone, 42 parts of clay, 26 parts of desulfurized gypsum, and 21 parts of fly ash.

[0057] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0058] (3) The finished cake is heated to 1150° C. at a heating rate of 10° C. / min and calcined for 30 min. The calcined product is then rapidly cooled by air and then ground through a 200-mesh sieve to obtain cement clinker.

[0059] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis. The results showed that the cement clinker included: dicalcium silicate: 71.95%, calcium sulfosilicate: 5.54%, dodecalyx heptahedralite: 15.31%, grossamite: 1.77%, glass phase: 4.33%, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0060] In accordance with GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 25.08 MPa, 28d compressive strength = 41.16 MPa.

[0061] Example 9 A method for preparing cement clinker comprises the following steps: (1) Take the following raw materials in parts by weight: 68 parts of limestone, 32 parts of clay, 29 parts of desulfurized gypsum, 37 parts of fly ash, and 29 parts of fluorine-containing sludge (purchased from Anhui Tongxin Recycling Resources Co., Ltd., with a fluorine content of 23.7 wt.%).

[0062] (2) Dry the above raw materials at 80°C for 12 hours, then grind them through a 200-mesh sieve. Press the obtained cement raw materials into cakes.

[0063] (3) The finished cake is heated to 1150° C. at a heating rate of 10° C. / min and calcined for 50 min. The calcined product is then rapidly cooled by air and then ground through a 200-mesh sieve to obtain cement clinker.

[0064] The cement clinker prepared in this embodiment was subjected to an XRD test and then to a Rietveld quantitative analysis, and the results showed that the cement clinker included: 46.45% dicalcium silicate, 22.28% calcium fluoride sulfide silicate, 19.67% tricalcium aluminate, 5.95% grossamite, 3.88% glass phase, and the remainder included unreacted raw materials, unavoidable impurities, etc.

[0065] According to GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 1d and 28d compressive strengths of the cement clinker prepared in this embodiment were tested, and the results were: 1d compressive strength = 21.87 MPa, 28d compressive strength = 45.64 MPa.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A dicalcium silicate-calcium fluoride-dodecalcium silicate heptaaluminate cement clinker, characterized in that: Calculated by mass percentage, the following mineral phases are included: 45-68% of dicalcium silicate, 14-26% of calcium fluorosulfosilicate, 12-22% of dodecaluminate heptacalcium, 1-5% of grossamite, 2-6% of glass phase, and the remainder includes unreacted raw materials and unavoidable impurities.

2. The method for preparing the dicalcium silicate-calcium fluoride-dodecalcium heptaaluminate cement clinker according to claim 1, characterized in that: The method comprises the following steps: taking calcium source, silicon source, gypsum, aluminum source and fluorine-containing sludge as raw materials, mixing them evenly in proportion and then calcining them; after completion, rapidly cooling the calcined product and then grinding it to obtain the cement clinker.

3. The method for preparing dicalcium silicate-calcium fluoride-dodecalcium silicate heptaaluminate cement clinker according to claim 2, characterized in that: The proportions of the components in the raw materials are: 57-85 parts by weight of calcium source, 30-48 parts by weight of silicon source, 18-35 parts by weight of gypsum, 16-27 parts by weight of aluminum source, and 14-32 parts by weight of fluorine-containing sludge; optionally, the fineness of the components is not less than 200 mesh.

4. The method for preparing dicalcium silicate-calcium fluoride-dodecalcium silicate heptaaluminate cement clinker according to claim 2, characterized in that: The calcium source includes at least one of limestone, marl, chalk, alkali slag and carbide slag.

5. The method for preparing dicalcium silicate-calcium fluoride-dodecalcium heptaaluminate cement clinker according to claim 2, characterized in that: The silicon source includes at least one of stripping soil, silica ash, coal gangue, clay, quartz sand and diatomaceous earth.

6. The method for preparing dicalcium silicate-calcium fluoride-dodecalcium silicate heptaaluminate cement clinker according to claim 2, characterized in that: The gypsum includes at least one of desulfurized gypsum, phosphogypsum, fluorinated gypsum, borogypsum and titanium gypsum.

7. The method for preparing dicalcium silicate-calcium fluoride-dodecalcium heptaaluminate cement clinker according to claim 2, characterized in that: The aluminum source includes at least one of bauxite, fly ash, aluminum ash, and coal gangue.

8. The method for preparing dicalcium silicate-calcium fluorosulfosilicate-dodecalcium heptaaluminate cement clinker according to claim 2, characterized in that: The fluorine content in the fluorine-containing sludge is not less than 15wt.%.

9. The method for preparing dicalcium silicate-calcium fluorosulfosilicate-dodecalcium heptaaluminate cement clinker according to any one of claims 2 to 8, characterized in that: The calcination temperature is 1100-1200° C., and the calcination time is 15-60 minutes.

10. The method for preparing dicalcium silicate-calcium fluorosulfosilicate-dodecalcium heptaaluminate cement clinker according to any one of claims 2 to 8, characterized in that: The cement clinker is ground to a fineness of not less than 200 meshes.

Citation Information

Patent Citations

  • Method for preparing fluoaluminate cement from fluorine-containing sludge

    CN102795795A

  • Baric white sulphoaluminate cement clinker and preparation method thereof

    CN109265031A

  • White sulfoaluminate cement clinker and preparation method thereof

    CN109369043A

  • Dicalcium silicate-calcium sulphoaluminate-calcium sulphosilicate cement clinker and preparation process thereof

    CN115849740A

  • Monocalcium silicate-calcium sulphosilicate-dicalcium silicate cement clinker, cement composition and preparation method of cement composition

    CN118479760A